2016
DOI: 10.1152/ajpregu.00061.2016
|View full text |Cite
|
Sign up to set email alerts
|

Garlic oil polysulfides: H2S- and O2-independent prooxidants in buffer and antioxidants in cells

Abstract: The health benefits of garlic and other organosulfur-containing foods are well recognized and have been attributed to both prooxidant and antioxidant activities. The effects of garlic are surprisingly similar to those of hydrogen sulfide (H2S), which is also known to be released from garlic under certain conditions. However, recent evidence suggests that polysulfides, not H2S, may be the actual mediator of physiological signaling. In this study, we monitored formation of H2S and polysulfides from garlic oil in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 67 publications
2
32
0
4
Order By: Relevance
“…It is in agreement with results of DeLeon et al who, in an assay based on the H 2 S-sensitive fluorescent dye 7-azido-4-methylcoumarin (AzMC), demonstrated that garlic oil and DATS, when used independently, cannot release H 2 S [35]. Interestingly, normoxic and hypoxic conditions showed comparable effects on H 2 S-release from garlic oil and DATS in the presence of Cys or GSH, jettisoning the idea of a crucial involvement of dioxygen.…”
Section: Resultssupporting
confidence: 91%
“…It is in agreement with results of DeLeon et al who, in an assay based on the H 2 S-sensitive fluorescent dye 7-azido-4-methylcoumarin (AzMC), demonstrated that garlic oil and DATS, when used independently, cannot release H 2 S [35]. Interestingly, normoxic and hypoxic conditions showed comparable effects on H 2 S-release from garlic oil and DATS in the presence of Cys or GSH, jettisoning the idea of a crucial involvement of dioxygen.…”
Section: Resultssupporting
confidence: 91%
“…In the aforementioned studies by Benavides et al [38], the real-time in vitro measurement of the H 2 S level was reported. Moreover, a recent study of DeLeon et al monitoring the formation of H 2 S and polysulfides from garlic oil in human embryonic kidney cells (HEK 293) revealed that administration of garlic oil to cells increased the intracellular polysulfide (sulfane sulfur) level but had a minimal effect on the H 2 S level [40]. Only after the addition of exogenous thiols (Cys, GSH) to cell culture, an increase in the H 2 S level was observed.…”
Section: Discussionmentioning
confidence: 99%
“…(De Martino, Filomeni, Aquilano, Ciriolo, & Rotilio, ), (DeLeon, Gao, Huang, & Olson, ; Ueda et al, ), (Y.‐L. Chu et al, )…”
Section: Introductionmentioning
confidence: 99%
“…For many years, they have been used to prevent and treat certain diseases such as diabetes, arthritis, colds and flu, cough, headache, hemorrhage, asthma, atherosclerosis, and inflammatory diseases (H. A. R. Suleria, Butt, Anjum, Arshad, & Khalid, 2013;Zeng et al, 2017). It has recently been noted that these vegetables, in addition to the conventional antibacterial, antifungal, antiviral, antiprotozoal, and antiworm effects, showed extensive in vitro and in vivo antiproliferative, antimotility, and cytotoxic potentials against cancer cells (Abdelrahman, Mahmoud, El-Sayed, Tanaka, & Tran, 2017; Chu et al, -Others antitumor effects (chelating irons, ↓p38 adhesion of tumor cells and metastasis, growth inhibition, cell cycle arrest, ↑ROS production and damaging to lipids and proteins, ↓MMP, antiangiogenesis, block cellular aging, hindering cellular division by expression of p38, ↓autophagy, ↓side effects of chemotherapy and radiotherapy, AMPK/ TSC2 expression and beclin-1 signaling pathways) (Thomson & Ali, 2003), (Saedi, Md Noor, Ismail, & Othman, 2014), (Oommen, Anto, Srinivas, & Karunagaran, 2004) (Grudzien & Rapak, 2018), (Ishikawa et al, 2006), (Lestari & Rifa'i, 2018) (Saud et al, 2016;Ziaei et al, 2015), (Hodge, Hodge, & Han, 2002), (Guan, Zhao, Xie, & Zeng, 2018) (Belloir, Singh, Daurat, Siess, & Le Bon, 2006), (Knowles & Milner, 2003) (De Martino, Filomeni, Aquilano, Ciriolo, & Rotilio, 2006), (DeLeon, Gao, Huang, & Olson, 2016;Ueda et al, 2002), (Y.-L. Chu et al, 2013) (Belloir et al, 2006), (Yamazaki et al, 1992) (Saud et al, 2016;Ziaei et al, 2015), (Hodge et al, 2002) , (H.-S. Chang et al, 2012), (Sowjanya, Devi, & Madhavi, 2009;Upadhyay, 2017), (Lin et al, 2017), (Y.-L. …”
Section: Introductionmentioning
confidence: 99%